Dinâmica macroeconômica, receitas tributárias e fragilidade financeira: uma análise empírica recente para a cidade de Uberlândia/MG - Amaral, Kelmaisteis Wanderson Rodrigues Correa do (2021)
This work intends to analyse empirically the relationship between macroeconomic policies and municipal finances in the city of Uberlândia / MG in the period of 2006-2019. For this purpose, the Non-Linear auto-regressive Distributed Lag Model (NARDL) is used. This methodology is adequate because it allows analysing the finance in different aspects, mainly, because it is able to measure the asymmetric short or long term effects of an explanatory variable on the dependent variable. The results showed that: i) social spending has a greater positive impact on tax revenue in the aforementioned city, both in short and in the long terms; ii) federal government investments have a low impact on local revenue in all the estimates made in which this variable was significant; iii) the monetary policy has no effect on the taxation of city of Uberlândia / MG, also in short and long terms; and iv) in none of the analysed models did the exchange rate policy prove its capability of expanding municipal tax collection, however, the stable exchange rate policy proved to be the best strategy to not negatively affect tax collection in short or on long terms.